Comprehensive analysis of sequences of a protein switch. (1st July 2015) - Chen, Szu‐Hua; Meller, Jaroslaw; Elber, Ron
Abstract: Switches form a special class of proteins that dramatically change their three‐dimensional structures upon a small perturbation. One possible perturbation that we explore is that of a single point mutation. Building on the pioneering experimental work of Alexander et al . (Alexander et al. PNAS, 2007; 104, 11963–11968) that determines switch sequences between α and α+β folds we conduct a comprehensive sequence sampling by a Markov Chain with multiple fitness criteria to identify new switches given the experimental folds. We screen for switch sequences using a combination of contact potential, secondary structure prediction, and finally molecular dynamics simulations. Statistical properties of switch sequences are discussed and illustrated to be most sensitive to mutation at the N‐ and C‐ termini of the switch protein. Based on this analysis, a particularly stable putative switch pair is identified and proposed for further experimental analysis.